An empirical analysis of stock market integration: Comparison study of Singapore and Malaysia - YI, Zheng (Institutional Knowledge at Singapore Management University, 2009)
Using a GARCH (1,1) model, this paper compares the extent to which financial sector liberalization in Singapore and Malaysia each has led to integration of its domestic equity market with external markets. The results show that the level of integration of the domestic markets with the external markets is higher when MSCI regional and global data are used, as compared to when individual country data are used to proxy regional and global markets. Inferences are made about the preferred pace of liberalization in Singapore, as well as, the impact of the Asian financial crisis and capital control measures imposed in Malaysia on financial integration, in the respective countries under study.